A Genetic Tool to Quantify trans-Translation Activity in Vivo. Issue 23 (24th November 2017) - Macé, Kevin; Demay, Fanny; Guyomar, Charlotte; Georgeault, Sylvie; Giudice, Emmanuel; Goude, Renan; Trautwetter, Annie; Ermel, Gwennola; Blanco, Carlos; Gillet, Reynald
Abstract: In bacteria, trans- translation is the main quality control mechanism for rescuing ribosomes arrested during translation. This key process is universally conserved and plays a critical role in the viability and virulence of many pathogens. We developed a reliable in vivo double-fluorescence reporter system for the simultaneous quantification of both trans -translation and the associated proteolysis activities in bacteria. The assay was validated using mutant bacteria lacking tmRNA, SmpB, and the ClpP protease. Both antisense tmRNA-binding RNA and a peptide mimicking the SmpB C-terminal tail proved to be potent inhibitors of trans -translation in vivo . The double-fluorescent reporter was also tested with KKL-35, an oxadiazole derivative that is supposed to be a promising trans -translation inhibitor, and it surprisingly turns out that trans -translation is not the only target of KKL-35 in vivo . Graphical abstract: Image 1 Highlights: Novel reporter systems are needed for the rapid development of new antimicrobial drugs. Inhibitors of trans -translation may act as antibiotics. We developed and validated a double-fluorescence reporter system for simultaneous and specific detection of bacterial trans -translation and proteolysis activity. Trans -translation is not the only target of KKL-35 in vivo.